Pengembangan Aplikasi Mobile Terintegrasi Vending Machine Untuk Menangani Permintaan Barang Pada Field Company - Mareta, Prisicilia (E-Jurnal Universitas Samudra, 2024)
Currently, the process of requesting field supplies is still hindered by complex manual administration, resulting in delays and inefficiencies. In this work, the mobile application has been successfully developed as a solution to improve stock management efficiency to meet the operational needs of field industry companies. The purpose of this application is to provide convenience to field employees in the process of requesting exchanges and ordering items such as safety shoes, safety helmets, gloves, and other items. Through the implementation of the RAD method in development, this application then has successfully integrated vending machine technology, the application, and the website, resulting in ease and speed in the item request system and convenience for field employees in taking orders for field equipment. Besides, this developed system will reduce administrative burdens related to the management of requested items by field employees. With this service, efficiency and faster service can be enhanced, as all processes are conducted through the mobile application